CDMA-based predictive model of the read performance of EPC RFID tags in supply chain environments. (2nd April 2008) - Magana, Mario E.; Porter, J. David; Kim, David S.
Radio Frequency Identification (RFID) technology is quickly becoming the item-tracking solution of choice in supply chain applications. However, most RFID deployments are currently performed on a trial-and-error basis. This research aims to develop a predictive model of the read performance of Electronic Product Code (EPC) RFID tags in supply chain environments borrowing ideas from well established cellular communication systems that are based on Code Division Multiple Access (CDMA) technology. This predictive model will be used to determine the optimal number of tags that can be consistently read in a specific warehouse facility prior to the deployment of an RFID system solution.